Endogenous Growth with Endogenous Fertility and Social Discrimination in Education - Andreas Schäfer (Universität Rostock, Institut für Volkswirtschaftslehre, 2002)
We simulate a two-sectoral, three-period OLG-model with endogenous fertility and endogenous education. Parents receive utility from quantity and quality (education) of their offspring, generating a trade-off between the former and the latter. Since education governs efficiency in production, hence wage income and growth, labour supply and education per child increase and fertility declines dur- ing the process of economic development. Therefore, the model is able to explain the recent fertility decline, in all developed countries, and to single out the determinants for long-run growth in per capita terms. The transition speed towards the steady state is governed by the growth rate of the wage rate, which in turn depends on education investments and fertility of previous generations, leading to an intergenerational persistence in these variables. Due to this effect, social discrimination in the education sector leads to high fertility and low education in the low-income percentiles, while the opposite is true for the upper ones. Hence, the average level of education declines and hinders growth.
Keywords: 330; Bevölkerungsökonomie; Bildungsökonomik; Overlapping Generations; Neue Wachstumstheorie; Fertilität; Bildungschancen; Diskriminierung; Theorie